Evaluation of Knowledge and Skills Retention on Basic Emergency Obstetric and Newborn Care Among Skilled Birth Attendants in Selected Counties of Western Kenya - Kibiwott, Doris; Sum, Ann Mwangi; Kang'ethe, Simeon (East African Journal of Nursing, 2024)
Maternal mortality remains a pressing concern in the African Region, with preventable deaths occurring every two minutes globally. Despite concerted efforts to mitigate this issue, the African Region continues to grapple with a high maternal mortality ratio, particularly in sub-Saharan Africa. The Liverpool School of Tropical Medicine (LSTM) has trained skilled birth attendants (SBA) since 2017 to reduce maternal deaths to 70/100,000 live births. However, Kenya still reported a high maternal death rate of 362/100,000 live births (KDHS 2022) which is unacceptably high and this prompted an investigation into whether knowledge and skills deterioration one year after training contribute to this high mortality rate. This study sought to evaluate the retention rate of knowledge and skills from BEmONC training among skilled birth attendants in Kisumu and Vihiga counties. The theoretical framework adopted for this study was Kirkpatrick’s four training evaluation levels. A cross-sectional quantitative method was used in the randomly selected health facilities in Kisumu and Vihiga counties. The study population consisted of skilled birth attendants trained in Basic Emergency Obstetrics and Newborn Care (BEMNOC) one year before this study. A sample size of 170 was determined using Fisher’s formula and selected by simple random sampling. Data was collected using a pretested self-administered questionnaire featuring multiple choice questions for knowledge assessment, a checklist for partograph completeness, and case scenarios for skills evaluations. Quantitative data was summarized using proportions and median while inferential statistics was carried out using logistic regressions. Quality of care (QoC) was assessed against international best practices and standards with a cut-score set at >70% correct answers, determined by the criterion-referenced test evaluation model adopted from the Modified Angoff (1971) methodology. Out of the 170 SBA, the response rate was 88%. The majority of the respondents were female (69.8%), aged between 30-34 years (29.3%), and held diploma-level education (59.7%). Overall median knowledge retention at 36.9%, skills retention at 58.64%, and partograph completion at 52.9% all falling below the study’s retention rate benchmark of over 70%. The years after BEmONC training and BEmONC retention rate had a statistically significant relationship (OR;95% CI: 0.45;0.19- 1.08, p=0.047) among those between 2-3 years since training. The knowledge and skills retention did not meet the > 70 % expected pass rate. However, skills retention showed higher retention as compared to knowledge Recommendations: There is a need for regular refresher training, supportive supervision, and improved institutional support to enhance the quality of care provided by skilled birth attendants